An Insight into the Immunization Coverage for Combined Vaccines in Albania - Pojani, Eftiola; Nelaj, Erida; Ylli, Alban (European Scientific Journal, ESJ, 2017)
We aim to Provide facts about the vaccination coverage for combined vaccines such as MMR (Measles, Mumps and Rubella) and DTP (Diphtheria, Tetanus, Pertussis) containing vaccines in use in Albania during the last 10 years, in order to confirm the stability of immunization program. One of the reasons for coverage improvement is the use of one or two-dose vials for the administration of MMR vaccine, enabling the vaccination of children at any time, without the need of gathering them on certain days when the multi-dose vaccine vials are opened. In the last three years, according to WHO recommendations, it was noted that vaccination coverage with three doses containing DTP is at sustainable levels, always above 95%, but for our country this value goes sometimes above 98%. As for the use of pentavalent vaccine, from 2008, DTP-HepB-Hib, also the coverage of Hepatitis b vaccine is always at upper levels due to its use on 5 in 1 combination. The application of this vaccine was associated with the use of one dose vial administration, therefore one vaccine to a child. Immunization coverage for vaccines with measles component remains at very high levels for both doses of vaccine, more then 95%. Immunization coverage for vaccines with DTP component exceeds 95% rate at country level, for each district it exceeds 95% and it reaches the value of 98.5% for the last two years. During the last years the vaccine coverage is increased significantly as a result of using combined vaccine of DTP-HepB -Hib. The use of one dose vials has played an important role on sustaininig and increasing vaccination coverage.